2021
DOI: 10.1016/j.jiac.2021.02.026
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-associated pulmonary aspergillosis in a Japanese man: A case report

Abstract: CAPA (COVID-19 associated pulmonary aspergillosis) is an important complication of COVID-19. It has been reported that the incidence of CAPA is as high as 19%e33% worldwide. However, its onset has not been reported in Japan. A 72-year-old Japanese man was diagnosed with COVID-19 and was transferred to our hospital due to deterioration of respiratory condition. Treatment with remdesivir, dexamethasone (DEXA), and antibiotics was performed under mechanical ventilation. Although the condition improved temporarily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The characteristics of the 57 eligible studies is presented in Table 1 (case reports, n = 33 and case series, n = 3) & Table 2 (cohort-studies, n = 21). Most of the studies published were from the five continents that included Europe [n = 24, 42.1%] (Denmark [ 23 ], Italy [ 27 , 34 , 35 ], Ireland [ 29 ], France [ 30 , 69 , 75 ], Spain [ 31 , 45 , 71 ], Greece [ 51 ], Austria [ 54 ], Netherlands [ 55 , 57 ], Germany [ 58 , 63 , 67 ], UK [ 62 , 64 , 78 ], Switzerland [ 74 , 77 ]), Asia [n = 18, 31.5%] (Iran [ 24 , 28 , 68 , 76 ], Iraq [ 39 ], Kuwait [ 33 ], Qatar [ 40 , 53 ], Japan [ 41 , 42 ], India [ 18 , 43 , 46 , 48 , 59 ], Indonesia [ 49 ], China [ 60 ], Pakistan [ 65 ]), North America [n = 10, 17.5%] (USA [ 26 , 32 , 36 , 38 , 44 , 50 , ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of the 57 eligible studies is presented in Table 1 (case reports, n = 33 and case series, n = 3) & Table 2 (cohort-studies, n = 21). Most of the studies published were from the five continents that included Europe [n = 24, 42.1%] (Denmark [ 23 ], Italy [ 27 , 34 , 35 ], Ireland [ 29 ], France [ 30 , 69 , 75 ], Spain [ 31 , 45 , 71 ], Greece [ 51 ], Austria [ 54 ], Netherlands [ 55 , 57 ], Germany [ 58 , 63 , 67 ], UK [ 62 , 64 , 78 ], Switzerland [ 74 , 77 ]), Asia [n = 18, 31.5%] (Iran [ 24 , 28 , 68 , 76 ], Iraq [ 39 ], Kuwait [ 33 ], Qatar [ 40 , 53 ], Japan [ 41 , 42 ], India [ 18 , 43 , 46 , 48 , 59 ], Indonesia [ 49 ], China [ 60 ], Pakistan [ 65 ]), North America [n = 10, 17.5%] (USA [ 26 , 32 , 36 , 38 , 44 , 50 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Case report and case series: Based on the methodological quality & synthesis guide, twenty-four (72.7%) case reports were having low [ 18 , 23 31 , 33 – 35 , 37 , 38 , 40 , 41 , 43 45 , 49 , 52 54 ] and nine (27.2%) case reports were having medium risk of bias [ 32 , 36 , 39 , 42 , 46 48 , 50 , 51 ]. Whereas, all the three cases series were having low risk of bias [ 55 57 ] ( S3 Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The main diagnostic criteria used were AspICU [103] (seven studies) and modified AspICU (eight studies) [104]. The patients were predominantly male (49, 66.2%) and had a median age of 69 years (inter-quartile range (IQR) [57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74]. The reported major co-morbidities were arterial hypertension (37 patients, 50%), diabetes mellitus (26, 35.1%), chronic pulmonary disease (13, 17.5%), cardiovascular disease (9, 12.2%), and obesity (4, 5.4%).…”
Section: Case Reports and Case Seriesmentioning
confidence: 99%
“…The ECMM expert guidelines have recommended voriconazole or isavuconazole as recommended first-line therapy for suspected and confirmed COVID-19-associated pulmonary Aspergillosis [ 40 ]. In a kidney transplant patient diagnosed with invasive pulmonary Aspergillosis, the patient showed recovery following treatment with isavuconazole and nebulized pulmonary amphotericin B combination and removal of immunosuppression [ 41 ]. Another case report of Aspergillosis in a post-COVID-19 patient suggested that pulmonary resection may be the last and most effective strategy to manage the disease.…”
Section: Resultsmentioning
confidence: 99%